1983
DOI: 10.1111/j.1399-3054.1983.tb06277.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brassinosteroid on auxin‐induced ethylene production by etiolated mung bean segments

Abstract: 1983. The effect of brassinosteroid on auxin-induced ethylene production by etiolated mung bean segments. -Physiol. Plant. 59: 539-544.Brassinosteroid, an analogue of brassinolide, (BR) (2a, 3a. 22|5, 23(5-tctrahydroxyindole-3-acctic acid (IAA), naphthaleneacetic ac-id (NAA), 2,4-dichlorophcnoxyacetic acid (2.4-D), indolc-3-butyric acid (IBA). indole-3-propionic acid (IPA). indole-3-pyruvic acid (IPyA), indole-3-aldchydc (tAld), indolc-3-carbiiiol (tCB) or tryptophan (TRP) lor its effects on ethylene piodticti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
3
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 19 publications
(10 reference statements)
5
38
3
2
Order By: Relevance
“…It is known that epidermal cell death in nodes correlates with root emergence in rice and it is mediated by ethylene (Steffens and Sauter, 2009). Since ethylene biosynthesis is activated by BR (Arteca et al, 1983;Yi et al, 1999), this observation may be a BR effect mediated via ethylene biosynthesis. Moreover, most of BU1:OX plants displayed severe sterility.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that epidermal cell death in nodes correlates with root emergence in rice and it is mediated by ethylene (Steffens and Sauter, 2009). Since ethylene biosynthesis is activated by BR (Arteca et al, 1983;Yi et al, 1999), this observation may be a BR effect mediated via ethylene biosynthesis. Moreover, most of BU1:OX plants displayed severe sterility.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the BR-induced bending and inclination can be inhibited by high concentration of IAA transport inhibitor 2,3,5-triiodobenzoic acid (Cao and Chen, 1995;Takeno and Pharis, 1982). The ethylene production by etiolated mung bean hypocotyls is also synergistically promoted by BRs and auxin (Arteca et al, 1983). These physiological observations suggest a cross-talk between BRs and auxin.…”
mentioning
confidence: 86%
“…Brassinosteroids are known to act synergistically with auxin to stimulate cell elongation (Katsumi, 1985;Sasse, 1990) and ethylene production (Arteca et al, 1983), suggesting that their effects are mediated by auxin (Takeno and Pharis, 1982) or that brassinosteroids enhance tissue sensitivity to auxin (Mandava, 1988). Despite indirect evidence that the mode of action of brassinosteroids is different from that of auxin (Katsumi, 1991), there are indications that brassinosteroids may somehow influence the endogenous auxin content.…”
Section: Introductionmentioning
confidence: 97%
“…These hormones affect several biological processes, including stem elongation, pollen tube growth, leaf bending, root growth, and xylem formation (Yokota, 1997). These developmental activities are mainly associated with ATPase activity (Cerana et al, 1983), synthesis of 1-aminocyclopropane-1-carboxylic acid synthase (Arteca et al, 1983), alteration in microtubule orientation (Mayumi and Shibaoka, 1995), and modification of cell walls (Zurek et al, 1994). Clouse and Zurek (1991) observed that exogenously supplied brassinolide, the most active brassinosteroid, promoted both tracheary element differentiation and cell division in cultured tuber explants.…”
Section: Introductionmentioning
confidence: 99%